Non‐Halogenated‐Solvent Processed and Additive‐Free Tandem Organic Solar Cell with Efficiency Reaching 16.67%. (8th April 2021) - Qin, Shucheng; Jia, Zhenrong; Meng, Lei; Zhu, Can; Lai, Wenbin; Zhang, Jinyuan; Huang, Wenchao; Sun, Chenkai; Qiu, Beibei; Li, Yongfang
Abstract: Organic solar cells (OSCs) have recently reached a remarkably high efficiency and become a promising technology for commercial application. However, OSCs with top efficiency are mostly processed by halogenated solvents and with additives that are not environmentally friendly, which hinders large‐scale manufacture. In this study, high‐performance tandem OSCs, based on polymer donors and two small‐molecule acceptors with different bandgaps, are fabricated by solution processing with non‐halogenated solvents without additive. Importantly, the two active layers developed from non‐halogenated solvents show better phase segregation and charge transport properties, leading to superior performance than halogenated ones. As a result, a tandem OSC with high efficiency of up to 16.67% is obtained, showing unique advantages in future massive production. Abstract : Two new small‐molecule acceptors with different bandgaps are designed and synthesized for application in front and rear cells in tandem organic solar cells (OSCs) processed by non‐halogenated solvents. When cooperating with appropriate polymer donors, the tandem OSCs processed by non‐halogenated solvents demonstrate a power conversion efficiency of 16.67%.